A 59-year-old Female Post Bariatric Surgery with Severe Vitamin D Deficiency and Severe Hypocalcemia Induced by Denosumab Injection for Osteoporosis. Issue 6 (2018) - Beal, John; Holland, Soemiwati W; Chalasani, Krishna; Hossain, Mohammad A
No abstract available